Analysis on Cage Dynamic Characteristic of Angular Contact Ball Bearing During Deceleration - Wenbing Tu; Haibin He; Leping Liu; Ya Luo (Jixie chuandong)
The deceleration process generally exists in the feed system of CNC machine, and the speed change of the process has a great influence on the dynamic performance of angular contact ball bearing, which has always been little noticed by scholars at home and abroad. Taking angular contact ball bearing 7603025 as investigation object, a dynamics analysis model of multi-rigid-body for angular contact ball bearing is established. Based on Adams software, the influence of radial force, axial force and angular acceleration on its dynamic characteristics in the deceleration process is analyzed, which are the speed and centroid trajectory of cage, and the contact force between rolling ball and cage. The study results show that the increase of radial force, the decrease of axial force and the increase of angular acceleration will lead to the increase of collision force between rolling ball and cage, which leads to the skidding in bearings and the shaking of cage more seriously, and the fluctuation range of cage rotational speed curve larger.